Application of gold nanomaterials for ionizing radiation detection. (26th January 2022) - Shiratori, Daiki; Nakauchi, Daisuke; Kato, Takumi; Kawaguchi, Noriaki; Yanagida, Takayuki
Abstract: Au nanomaterials are known to change their properties significantly depending on their particle size. The prepared chloride glasses exhibited yellow emission (520 nm) upon UV rays (250 nm) irradiation, and the intensity of emission was found to decrease with X-ray dose. We concluded that this is because luminescent Au nanoclusters (AuNCs) of a few nanometers in size grow into Au nanoparticles (AuNPs) of a few tens of nanometers in size due to the photoreduction effect induced by irradiating X-ray, and the absorption (550 nm) attributed to the surface plasmon effect of AuNPs make decrease the AuNCs emissions. From the results of the changes of photoluminescence (PL) intensity concerning the irradiation X-ray dose, it was found that the PL intensity monotonically decreased 3000 mGy or more. This suggests that the Au-doped CsCl–BaCl2 –ZnCl2 glass can act as an X-ray detection material in a specific dose region.